127 Impact of CYP2D6, CYP3A4, and CYP2C9 pharmacogenomic profile on pain relief and adverse events in Canadian children treated with oxycodone and ibuprofen. (29th October 2021) - Yukseloglu, Aran; Ali, Samina; Drendel, Amy; Carleton, Bruce; Ross, Colin; Le May, Sylvie; Manaloor, Robin; Rosychuk, Rhonda; Johnson, David
Abstract: Primary Subject area: Clinical Pharmacology and Toxicology Background: Genomic variation impacts drug pharmacokinetics for commonly used children's pain medications such as oxycodone and ibuprofen. In order to personalize and best treat children's pain, how cytochrome enzyme polymorphisms for CYP2D6, CYP3A4, and CYP2C9 impact clinical effectiveness and safety for oxycodone and ibuprofen were studied. Objectives: Primary objectives were to evaluate if allelic variations of CYP2D6, CYP2C9, and CYP3A4 would a) alter clinical effectiveness of ibuprofen and oxycodone for pain relief, and b) impact the occurrence of adverse events. Secondary objectives were to determine the degree to which these genetic and other clinical factors influence analgesic effectiveness and safety. Design/Methods: This prospective, observational cohort included children aged 4-16 years who were seen in a pediatric emergency department (between June 2010 - July 2014) with an acute fracture and used ibuprofen OR oxycodone for at-home pain management. Saliva samples were obtained prior to discharge, and daily telephone follow-up collected self-reported pain scores, medication use, adverse events, and functional limitations for 3 days. Genotyping identified allelic variants of CYP2D6, CYP3A4, and CYP2C9. Pain was measured using the Faces Pain Scale-Revised. CYP2D6 metabolic phenotypes were determined based on identified variants. Regression analyses were employed to determine relationships between clinical and genomic patient characteristics, pain relief, and adverse events. Results: We included 210 children (n=140 ibuprofen, n=70 oxycodone); mean age was 11.1 (±3.5) years, 66.2% were male, and 79.5% self-identified as Caucasian. The median pain reduction in the ibuprofen group was 4 (±2.0) and 4 (±3.5) in the oxycodone group on Day 1 (p = 0.69). Adverse events were experienced by 53.2% of the ibuprofen group and 78.3% of the oxycodone group (p < 0.001). CYP2D6 Intermediate Metabolizers had significantly less pain relief using oxycodone than Extensive Metabolizers (p = 0.04). CYP3A4 variants did not significantly impact pain relief or adverse events. Those with the decreased functioning CYP2C9*2 allele experienced less adverse events compared to the normal functioning allele CYP2C9*1 (p = 0.003) when using ibuprofen. Males (p = 0.035) and all children using non-pharmacological pain strategies (p = 0.02) experienced less pain relief with oxycodone. Conclusion: A better understanding of pharmacogenomic variation could help personalize medication choice. Sex and non-pharmacologic pain management impact pain relief with oxycodone, warranting further study to better understand their relationship with opioid pain relief in children.